Contamination of Australian newborn calf carcasses at slaughter with Clostridium difficile. (March 2016) - Knight, D.R.; Putsathit, P.; Elliott, B.; Riley, T.V.
Abstract: In North America and Europe, reports of a genetic overlap between toxigenic strains of Clostridium difficile isolated from humans, livestock and retail meat suggest that food-borne transmission may be occurring. We investigated the prevalence, concentration and genetic diversity of C. difficile on the carcasses ( n = 300) and in the faeces ( n = 30) of neonatal veal calves at three abattoirs in Australia in 2013. Selective culture (both direct and enrichment) was performed, and all isolates were characterized by PCR for the toxin genes tcdA, tcdB and cdtA/B and by PCR ribotyping. Prevalence of C. difficile was 25.3% (76/300) on carcasses and 60.0% (18/30) in faeces. Multiple PCR ribotypes (RT) were detected, with four binary toxin-positive RTs accounting for 70.3% (71/101) of isolates; 127 (A +, B +, CDT +, 32.7%), 288 (A –, B –, CDT +, 28.7%), 033 (A –, B –, CDT +, 6.9%) and 126 (A +, B +, CDT +, 2.0%). Viable counts of a subset of samples revealed detectable numbers of C. difficile in 66.7% (10/15) of faecal samples (range 2.0 × 10 3 to 2.3 × 10 6 CFU/mL, median count 2.5 × 10 4 CFU/mL) and in 16.7% (25/150) of carcase samples (range 3 to 33 CFU/cm 2, median count 7 CFU/cm 2 ). These data further confirm that Australian neonatal veal calf carcasses are contaminated with potentially significant strains of C. difficile at slaughter.